Програма інноваційного освітнього проєкту з формування самоефективності суб'єктів освітнього процесу засобами вальдорфської педагогіки - Резунова, Олена Сергіївна; Rezunova, Olena; Передерій, Ольга Леонідівна; Perederii, Olha (Дрогобицький державний педагогічний університет імені Івана Франка, 2022)
Соціальні трансформації третього десятиріччя ХХІ ст. призвели до потреби сучасного суспільства в індивідах, які здатні досягати поставлених цілей з найменшими затратами часу і ресурсів, бути успішними у різних видах діяльності, мати розвинені навички саморегуляції, самопідтримки та самоконтролю. Авторками статті робиться спроба довести, що впровадження інноваційних освітніх проектів в навчально-виховний процес закладів освіти сприятиме реформації системи освіти та покращенню якості освітнього процесу. У дослідження зазначено, що педагогічна система «Вальдорфська школа» створює сприятливі умови для цілісного формування та самоформування особистості та збереження фізичного, психічного та духовного здоров’я дитини. В статті доведено актуальність розробленого інноваційного освітнього проєкту, зазначено його мету, гіпотезу, етапи, завдання та методи. Визначено основні принципи реалізації проєкту, а саме: гуманістична спрямованість освітнього процесу; педоцентризм; цілісне охоплення природи людини; вікова; різнобічності і гармонійності; залучення почуттєвого переживання; поєднання соціального та індивідуального; поваги до дитини. Основними етапами реалізації просту є: організаційно-підготовчий; концептуально-діагностичний; формувальний; узагальнювальний. Охарактеризовано, що наукова новизна та теоретичне значення результатів проєкту буде полягати в теоретичному обґрунтуванні та експериментальній перевірці ефективності організаційно-педагогічних умов формування самоефективності суб’єктів освітнього процесу засобами вальдорфської педагогіки, а саме: концептуалізації формування самоефективності суб’єктів освітнього процесу засобами вальдорфської педагогіки(перша умова); моделювання формування самоефективності суб’єктів освітнього процесу засобами вальдорфської педагогіки(друга умова); технологізації формування самоефективності суб’єктів освітнього процесу засобами вальдорфської педагогіки (третя умова). Social transformations of the third decade of the XXI century led to an understanding of the need of modern society for individuals who are able to achieve their goals with the least expenditure of time and resources, to be successful in various types of activities, to have developed skills of self-regulation, self-support and self-control. The authors of the article attempt to prove that the introduction of innovative educational projects into the educational process of educational institutions will contribute to the reformation of the education system and the improvement of the quality of the educational process. The study states that the pedagogical system "Waldorf School" creates favorable conditions for the integral formation and self-formation of the personality and the preservation of the child’s physical, mental and spiritual health. The article proves the relevance of the developed innovative educational project, its purpose, hypothesis, stages, tasks and methods are indicated. The main principles of project implementation have been determined, namely: humanistic orientation of the educational process; pedocentrism; integral coverage of human nature; age; versatility and harmony; involvement of sensory experience; combination of social and individual; respect for the child. The main stages of the project implementation are: organizational and preparatory; conceptual and diagnostic; formative; generalizing. It is characterized that the scientific novelty and theoretical significance of the project results will consist in the theoretical substantiation and experimental verification of the effectiveness of the organizational and pedagogical conditions for the formation of the self-efficacy of the subjects of the educational process by the means of Waldorf pedagogy, namely: the conceptualization of the formation of the self-efficacy of the subjects of the educational process by the means of the Waldorf pedagogy (the first condition); modeling the formation of self-efficacy of the subjects of the educational process by means of Waldorf pedagogy (second condition); technologization of the formation of selfefficacy of the subjects of the educational process by means of Waldorf pedagogy (the third condition).
Innovative educational project program on the formation of self-efficiency of the subjects of the educational process using the means of waldorf pedagogy
Keywords: програма; program; інноваційний освітній проект; innovative educational project; суб’єкти освітнього процесу; subjects of the educational process; самоефективність; self-efficacy; вальдорфська педагогіка; Waldorf pedagogy